Development of a superconducting claw-pole linear test-rig. (3rd March 2016) - Radyjowski, Patryk; Keysan, Ozan; Burchell, Joseph; Mueller, Markus
Abstract: Superconducting generators can help to reduce the cost of energy for large offshore wind turbines, where the size and mass of the generator have a direct effect on the installation cost. However, existing superconducting generators are not as reliable as the alternative technologies. In this paper, a linear test prototype for a novel superconducting claw-pole topology, which has a stationary superconducting coil that eliminates the cryocooler coupler will be presented. The issues related to mechanical, electromagnetic and thermal aspects of the prototype will be presented.